Tecnologias da informação utilizadas pelos enfermeiros da atenção primária à saúde para organizar as ações de saúde frente à Covid-19 - Guedes, Haline Costa dos Santos (2022)
Introduction: The supply of health actions against the pandemic caused by covid-19 in Primary Health Care aims to increase access, early diagnosis, care for mild cases, and referral of moderate and severe cases to specialized services. Objective: To analyze the discourse of nurses regarding the use of information technology to organize health actions to confront covid-19 in Primary Health Care. Method: This is a study with a qualitative approach and exploratory design, with theoretical and methodological support from the French Discourse Analysis. The research was conducted with nurses from family health units belonging to the Sanitary Districts in the municipality of João Pessoa- PB. The data collection was carried out from September to November 2021 with 26 nurses, selected from the non-probabilistic sampling technique snowball technique. The empirical material was organized in the Atlas.ti 9 software and based on the theoretical and methodological contribution of the French Discourse Analysis. The project was approved under opinion number 4.827.540, with CAAE number 47670621900005188. Results: The participants had an average age of 43 years, 25 of them are female, with an average of 14 years of experience in Primary Care, among the interviewees 19 have specialization in family health. From the corpus, we identified discursive blocks related to the potential of information technology for nurses: innovation from social media; health education actions; resoluteness in daily actions. In addition to discursive blocks related to the difficulties in the use of technologies: digital literacy; barriers to the organization of health actions; professional devaluation. Conclusion: It was identified in the study that the nurses who make up Primary Care during the covid-19 pandemic used information technology to organize their health actions in a positive way, proving to be a strategy that enables the development of management in health services and work processes. This enables us to reflect on how important the role of information technology is for the performance of quality, uniqueness and continuity of care, the production of indicators for decision making, teaching and research.